Ketahanan Komposit Kayu Plastik Polistirena terhadap Serangan Jamur Pelapuk Coklat Tyromyces palustris - Darma, I.G.K. Tapa; Hadi, Yusuf Sudo; Atmojo, Andri Tri (Institut Pertanian Bogor (IPB University), 2002)
Wood specimens, 50 x 25 x 15 mm were impregnated in styrene and vinil acetate solutions at four concentration levels, using tertbutyl hydroperoxide as acatalyst. The specimens were dried at 60°C for 48 hours after which the solution was polymerized in situ. All specimens, including untreated specimens as control and specimens impregnated with Impralit CKB, were exposed to monoculture a brown rot fungus Tyromyces palustris, a brown rot fungus for 3 months. All wood polymer composite (WPC) specimens obviously showed higher resistance compared with the control. At four concentration levels, WPC of tusam showed excellent result with weight loss value less than specimens treated with Impralit CKB. WPC of karet (Hevea brasiliensis Muell. Arg) and sengon (Paraserianthes falcataria) showed good resistance at high styrene concentration level.